2015
DOI: 10.3389/fpsyt.2015.00104
|View full text |Cite
|
Sign up to set email alerts
|

Mental Imagery and Post-Traumatic Stress Disorder: A Neuroimaging and Experimental Psychopathology Approach to Intrusive Memories of Trauma

Abstract: This hypothesis and theory paper presents a pragmatic framework to help bridge the clinical presentation and neuroscience of intrusive memories following psychological trauma. Intrusive memories are a hallmark symptom of post-traumatic stress disorder (PTSD). However, key questions, including those involving etiology, remain. In particular, we know little about the brain mechanisms involved in why only some moments of the trauma return as intrusive memories while others do not. We first present an overview of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 110 publications
0
23
0
1
Order By: Relevance
“…Emotional imagery is a key induction context when investigating individual differences in emotionality, such as posttraumatic stress disorder (PTSD; e.g. Clark & Mackay, ), since developing a script that describes a personally relevant traumatic event can often target the trauma more precisely than seeking to find an appropriate scene. Early PET studies reported differences in functional activity based on whether narrative imagery involved personally relevant (autobiographical) or “standard” (fictitious) scenes, with personally relevant scenes prompting a significant amygdala activation (Fink et al, ; Markowitsch et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional imagery is a key induction context when investigating individual differences in emotionality, such as posttraumatic stress disorder (PTSD; e.g. Clark & Mackay, ), since developing a script that describes a personally relevant traumatic event can often target the trauma more precisely than seeking to find an appropriate scene. Early PET studies reported differences in functional activity based on whether narrative imagery involved personally relevant (autobiographical) or “standard” (fictitious) scenes, with personally relevant scenes prompting a significant amygdala activation (Fink et al, ; Markowitsch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional imagery is a key induction context when investigating individual differences in emotionality, such as posttraumatic stress disorder (PTSD; e.g. Clark & Mackay, 2015), since developing a script that describes a personally relevant traumatic event can often target the trauma more precisely than seeking to find an appropriate scene. Early PET studies reported differences in functional activity based on whether | 3 of 14 SAMBUCO et Al.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis criteria for PTSD include both an immediate exposure to a traumatic event and also witnessing trauma (American Psychiatric Association, ). To examine early PTSD‐like symptoms, the trauma film paradigm is an ideal model to bridge the gap between nonclinical and clinical samples based on its strongly controllable setting (Clark & Mackay, ).…”
Section: Methodsmentioning
confidence: 99%
“…The potentially important role of negative MI as a maintenance factor of psychological disorders has been supported in studies with adults suffering from PTSD (Clark and Mackay 2015;Cockerham et al 2016;Morina et al 2013), obsessive-compulsive disorder (OCD; Da Silva 1986;Rachman 2007;Speckens et al 2007), social anxiety disorder (SAD, e.g., Hackmann et al 2000), agoraphobia (Day et al 2004), body dysmorphic disorders (Osman et al 2004), and depression (Holmes et al 2008;Morina et al 2011). The negative mental images may influence both behavior and cognitions.…”
Section: Introductionmentioning
confidence: 98%